2023
DOI: 10.2337/dc22-0885
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms Responsible for the Increase in Glucose Production and Ketone Formation Caused by Empagliflozin in T2DM Patients

Abstract: OBJECTIVE To examine the mechanisms responsible for the increase in glucose and ketone production caused by empagliflozin in patients with type 2 diabetes mellitus (T2DM). RESEARCH DESIGN AND METHODS Twelve subjects with T2DM participated in two studies performed in random order. In study 1, endogenous glucose production (EGP) was measured with 8-h infusion of 6,6,D2-glucose. Three hours after the start of 6,6,D2-glucose infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…We previously demonstrated that the increase in HGP is blunted in the denervated kidney, 11 providing evidence of an important role for renal nerves in generating the signal to the liver following SGLT2 inhibition. Consistent with a neural signal, we have shown that the increase in HGP is accompanied by an increase in total body norepinephrine turnover rate within 1–2 h after SGLT2 inhibitor administration, 8 consistent with a role for sympathetic activation in triggering the increase in HGP. Because the magnitude of increase in HGP did not correlate with the amount of glucose excreted in the urine, it is likely that the signal activated by UGE that stimulates HGP is an ON–OFF signal and that the amount of glucose in the urine, as opposed to the acute increase in urinary glucose concentration, is of less importance in activating this signal.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We previously demonstrated that the increase in HGP is blunted in the denervated kidney, 11 providing evidence of an important role for renal nerves in generating the signal to the liver following SGLT2 inhibition. Consistent with a neural signal, we have shown that the increase in HGP is accompanied by an increase in total body norepinephrine turnover rate within 1–2 h after SGLT2 inhibitor administration, 8 consistent with a role for sympathetic activation in triggering the increase in HGP. Because the magnitude of increase in HGP did not correlate with the amount of glucose excreted in the urine, it is likely that the signal activated by UGE that stimulates HGP is an ON–OFF signal and that the amount of glucose in the urine, as opposed to the acute increase in urinary glucose concentration, is of less importance in activating this signal.…”
Section: Discussionsupporting
confidence: 85%
“…is calculated using the Steele equation as previously described. [7][8][9] The change in HGP during the last hour of the study (i.e., 240-300 min) from baseline was considered the drug's effect on endogenous glucose production.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, lipolysis is stimulated, and ketone body production increases. Recently, it has been reported that the use of Empagliflozin in patients with T2DM leads to a decrease in serum insulin, an increase in glucagon, and an increase in serum ketone bodies [ 15 ]. Regarding ketone bodies, the “Super-fuel” hypothesis has been proposed, which suggests that serum ketone bodies can serve as an effective energy source for the myocardium, contributing to improved cardiac function in patients with T2DM [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This exacerbates the hypovolemic state of DKA, leading to elevated cortisol, epinephrine, and glucagon levels, which in turn further enhance insulin resistance, ketogenesis, and lipolysis 25 48. A recent study has shown an increase in norepinephrine turnover in response to SGLT-2 inhibitor use that can increase hepatic glucose production independent of changes in insulin and glucagon 49…”
Section: Pathophysiologymentioning
confidence: 99%
“… 25 48 A recent study has shown an increase in norepinephrine turnover in response to SGLT-2 inhibitor use that can increase hepatic glucose production independent of changes in insulin and glucagon. 49 …”
Section: Pathophysiologymentioning
confidence: 99%